PEMAKNAAN SLOGAN KOTA "SEMARANG SETARA" DALAM PERSPEKTIF MULTIKULTURALISME - Subekti, Slamet (Sabda: Jurnal Kajian Kebudayaan, 2013)
A slogan is made to support the image of the organization or personal identity, as well as the city. The study was based on literature sources lhat have been used to investigate the meaning of the slogan "Semarang Setara" according to the stakeholders. Meaning has been officially determined by the local government which means that Semarang will be able to place themselves equal to the other metropolitan cities in Indonesia. There is also an acronym SEmarang koTA sejahfeRA (Semarang Welfare City). Many responses come from academics who want to built the city of Semarang as Renaissance city on the one hand, and others expect the city ofSemarangs built based on environment al base for suslainable development paradigm. Meanwhile, there are many negative responses comparing semarang with other cities that face profanity. Based on the background conditions of mulliculturalism in Indonesia in general, then I propose the perspective of multiculluralism in the slogan "Semarang Setara". The proposed model is autonomous and critical multiculluralism as a frame of reference for stakeholders to make Semarang as a place for people to live is humanistic and harmonious environment.